THE STUDY OF MENTAL MODEL ON N-HEXANE-METHANOL BINARY SYSTEM (THE VALIDATION OF PHYSICAL CHEMISTRY PRACTICUM PROCEDURE) - Albaiti, A.; Liliasari, L.; Sumarna, O. (Jurnal Pendidikan IPA Indonesia, 2016)
N-hexane and methanol systen is one example of a binary system that shows the solubility properties of reciprocity. This study aimed to assess the mental model of a n-hexane-methanolbinary system. Interaction at the submicroscopic level between n-hexane and methanol molecules is described in the form of mental model. Penelitian ini menggunakan cloud point method untuk memperoleh data kesetimbangan cair-cair sistem n-heksana-metanol. This study used a cloud point method to obtain data on liquid-liquid equilibrium on the system of n-hexane-methanol. Research data showed the maximum critical temperature (above the consolute temperature) of this system was at 42.95 Â°C with Xmethanol = 0.475 (P= 715 mmHg). Data from the laboratory observations was representedas a symbolic level in the form of the curve of correlation between mole fraction of methanol with temperature in a phase diagram system of n-hexane-methanol. The curve that was formed was asymmetric. It indicated that the solubility of n-hexane in methanol was relatively small compared to the solubility of methanol in n-hexane. Mental model of the binary system of n-hexane-methanol in four curve areasin the form of visualization of the interaction between n-hexane and methanol molecules through London force. In thermodynamics, each component had the same chemical potential inboth phases at equilibrium state. This study results could have a contribution to form a mental model on the student as the prospective chemistry subject teachers.